(untitled) (Experimental biology, 2021)
The article presents a geobotanical characterization and floristic analysis of a promising association of medicinal plants Salvia aethiopis L from the right bank of the Kapshagai-Bakanas highway towards the Almaty region, from an altitude of 709 m above sea level, an open steppe zone of a herbaceous community. The results of the study showed that the life forms of the floristic composition of the region, which defined the first population, dominated by therophytes, i.e. one-or two-year plants, 32 species (46%), in second place hemicryptophytes, i.e., perennial plants are 28 species (41%), chamaephytes, i.e. bushes and shrubs – types of 8 (12%), and macrophanerophytes met only 1 species (Ulmus pinnato-ramosa Dieck.). From the zone of the second coenopopulation (CP 2), the plant Tulipa kolpakovskiana Regel, listed in the Red Book, fell. The identified CP 1, CP 2, and CP 3 were carried out on the right bank of the Kapshagai-Bakanas highway. In the sample field under study, Salvia aethiopis L. 215 individuals of the plant were identified, 55 individuals were identified in the first coenopopulation, 42 individuals in the second coenopopulation, and 33 individuals in the third coenopopulation. In the first coenopopulation, the number of young generative plants increased, in the second and third coenopopulations, a group of young vegetative plants was formed, and generative plants were rarely found, and in the second coenopopulation, senile individuals of the postgenerative period prevailed.